Experience with Diagnosis and Management of Distal Radioulnar Joint Instability - Hearon, Bernard F.; Frantz, Lisa M.; Helsper, Elizabeth A.; Morris, Harry A. (Journal of Wrist Surgery, 2021)
Objective The aim of this study is to review our cumulative experience with diagnosis and treatment of distal radioulnar joint (DRUJ) instability and to present our treatment algorithm.Materials and Methods Retrospective review identified 112 patients who had 126 episodes of care for DRUJ instability at a single institution over a 21-year period. Those diagnosed acutely or subacutely were treated with immobilization of the wrist and elbow for 6 weeks, while those with chronic instability had anatomic reconstruction of the dorsal and palmar radioulnar ligaments with tendon autograft or an alternative arthroscopic treatment with our thermal annealing technique. Short-term treatment failures and surgical complications were recorded. Nonparametric statistical tests were used to analyze key long-term outcome measures including ulnar wrist pain and DRUJ stability indicated by the dorsopalmar stress test.Results At mean 7-year follow-up, eight patients in the acute-injury cohort had statistically significant improvements in wrist pain and DRUJ instability (p < 0.001). In both the 22-patient anatomic reconstruction cohort and the 37-patient arthroscopically treated group, there were also statistically significant improvements in wrist pain and DRUJ stability (p < 0.001) at mean 9-year follow-up. The majority of patients in all three groups was satisfied with treatment outcome, though some required secondary procedures.Conclusion Early clinical diagnosis of DRUJ instability using the dorsopalmar stress test provides an opportunity for effective nonsurgical treatment. For chronic presentation, we recommend our arthroscopic thermal annealing technique for mild or moderate instability and open anatomic reconstruction of the radioulnar ligaments for severe instability.Level of Evidence This is a Level IV, therapeutic study.
Keywords: anatomic distal radioulnar joint reconstruction; arthroscopic thermal annealing; distal radioulnar joint instability; triangular fibrocartilage complex; ulnar-sided wrist pain